Iran's multi-faceted strategy in Deir ez-Zor: From fighting terrorism to creating a zone of influence - Hamidreza Azizi (Stiftung Wissenschaft und Politik (SWP), 2020)
One aspect of Iran's involvement in Syria that has come under the spotlight recently is Iran's growing presence and activities in Deir ez-Zor province in eastern Syria. Not only has Iran established its military presence in the region by deploying troops and constructing military bases, it has also been active in social, cultural, and economic spheres. Many observers believe that Iran's goal is to establish a 'land corridor' to connect the country to Lebanon via Iraq and Syria. Others argue that Iran is attempting to expand its ideological influence in Deir ez-Zor by promoting Shi'ism. However, the Islamic Republic is pursuing a multifaceted strategy in the area. Tehran wants to establish an economic corridor to the Mediterranean to play a role in China's Belt and Road Initiative (BRI). Iran is also trying to create a zone of influence in Syria's east while strengthening its deterrence against Israel and the United States. Preventing the revival of the so-called Islamic State (IS) remains another priority.
Keywords: 320